In and Out of Focus: An Urban Lens on COVID-19 in the Global South. (May 2022) - Heymann, David
How has COVID-19 affected the everyday lives of citizens in the global South? Through a visual narrative, this photographic essay brings forth the impact that the pandemic has had on the lives and livelihoods of the urban poor that has been 'out of focus', ranging from the urban emptiness of vacated streets to the hands-on community spirit to help those in need. This visual essay uses imagery sourced from city partners within the KNOW programme, to depict and compare urban realities before (in focus) and during (out of focus) the pandemic. By visually presenting the people and places in pre-pandemic circumstances, this piece juxtaposes localised lived experiences, alongside the disruption, inherent solidarity and urban inequalities that have arisen during the progression of the pandemic in the global South.